2000
DOI: 10.1590/s0100-204x2000000700007
|View full text |Cite
|
Sign up to set email alerts
|

Curso diário e sazonal das trocas gasosas e do potencial hídrico foliar em aceroleiras

Abstract: Este trabalho objetivou avaliar o curso diário e sazonal das trocas gasosas, da temperatura foliar e do potencial hídrico da acerola (Malpighia emarginata D.C.), no campo. O experimento realizou-se no município de Paudalho, PE. Os valores da transpiração e do potencial da água foram, de modo geral, mais elevados no início da manhã e no final da tarde; os da resistência difusiva e temperatura foliar foram menores no início da manhã e no final da tarde. Houve uma limitação das trocas gasosas com o ambiente, em d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Unlike the present study, in which the highest values were recorded at 15 h during the dry period, in a study by Nogueira et al (2000) On the contrary, the PAR that reached the leaves of V. americana plants remained constant during both seasons, with a mean of 35 µmol m-2s-1 during the dry season and 26 µmol m-2 s-1 during the rainy period (Figure 3). Of the global solar radiation reaching the canopy, only 5% has been found to revert to photosynthetically active radiation in V. americana leaves located in the understory forest This is common in regions with dense vegetation, where the growth and survival of tree species in the understory are limited, especially by the availability of irradiance (Marenco & Vieira, 2005).…”
Section: Resultscontrasting
confidence: 92%
“…Unlike the present study, in which the highest values were recorded at 15 h during the dry period, in a study by Nogueira et al (2000) On the contrary, the PAR that reached the leaves of V. americana plants remained constant during both seasons, with a mean of 35 µmol m-2s-1 during the dry season and 26 µmol m-2 s-1 during the rainy period (Figure 3). Of the global solar radiation reaching the canopy, only 5% has been found to revert to photosynthetically active radiation in V. americana leaves located in the understory forest This is common in regions with dense vegetation, where the growth and survival of tree species in the understory are limited, especially by the availability of irradiance (Marenco & Vieira, 2005).…”
Section: Resultscontrasting
confidence: 92%
“…On the other hand, the accumulation of osmoregulators contributes to reducing Y w , helping to maintain the water status, but the organic solutes studied here did not accumulate in sufficient amounts to induce alterations in leaf Y w to genotype 14-CPA. Nogueira et al (2000), while studying two genotypes of the Barbados cherry in the field, observed variations in the Y w throughout the day. Similar to these studies, the authors verified the most negative values of water potential at noon in both genotypes, independent of seasonality, although the minimum values occurred in dry season and the genotype UFRPE 8 showed the lowest value (-4.32 MPa).…”
Section: Discussionmentioning
confidence: 99%
“…These authors observed that plants grown during summer showed higher transpiration values. Nogueira et al (2000) verified significant increases in water demand in acerola due to increase of the transpiration rate in the season of higher temperature, lower relative humidity and lower rainfall.…”
Section: Resultsmentioning
confidence: 84%